Velociraptor the speedy tale - Bromage, Fran; Forshaw, Louise (Essex, England Miles kelly, 2018)
Vicky is a super-speedy Velociraptor who races through life, and often straight into trouble. When Vicky loses sight of her family, she's in a hurry to find them but she'll need to slow down before she can join them again. This fabulous story features stunning artwork from Louise Forshaw and is a terrific read for any little dinosaur fan
English stories
2
Keywords: Dinosaurs -- Juvenile fiction; velociraptor -- Juvenile fiction